Ultra-poor Graduation Midline Survey in Somalia, 2023 - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset comes from the midline survey of a randomized impact evaluation of the Ultra-Poor Graduation (UPG) Model implemented by World Vision Somalia in internally displaced persons (IDP) camps in Baidoa, Somalia. The UPG program supports extremely vulnerable households through a combination of cash transfers, savings groups, productive asset or skills training, and life-skills coaching.